2009
DOI: 10.1124/mol.109.059006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dynamin-2-Mediated Endocytosis as a New Target of Osteoporosis Drugs, Bisphosphonates

Abstract: Nitrogen-containing bisphosphonates are pyrophosphate analogs that have long been the preferred prescription for treating osteoporosis. Although these drugs are considered inhibitors of prenylation and are believed to exert their effects on bone resorption by disrupting the signaling pathways downstream of prenylated small GTPases, this explanation seems to be insufficient. Because other classes of prenylation inhibitors have recently emerged as potential antiviral therapeutic agents, we first investigated her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Cleaved Notch3 is a key determinant of Notch3 biology, and DNM-mediated endocytosis is required for Jagged1-mediated Notch3 activation. Targeting Notch3 pathway activation with DNM inhibitors (20) combined with paclitaxel could be considered for future clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaved Notch3 is a key determinant of Notch3 biology, and DNM-mediated endocytosis is required for Jagged1-mediated Notch3 activation. Targeting Notch3 pathway activation with DNM inhibitors (20) combined with paclitaxel could be considered for future clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Of clinical interest, mutations in dynamin’s PH domain are associated with dominant intermediate Charcot-Marie-Tooth disease (Zuchner et al, 2005). Moreover, it has been demonstrated that alendronate, a nitrogen-containing bisphosphonate commonly used to treat bone loss associated with osteoporosis, binds dynamin’s PH domain and inhibits dynamin’s catalytic activity (Masaike et al, 2010). These reports further support the idea that the interaction of the dynamin PH domain with Pyk2 potentially inhibits the GTPase activity of dynamin.…”
Section: Discussionmentioning
confidence: 99%
“…The AX-ALN solution prepared in our laboratory contained 10% labeled ALN and 90% free ALN. Cells were incubated with AX-ALN or F-ALN (10 K4 , 10 K5 , and 10 K6 M) in the presence or absence of 100 mM DC and 20 mM chlorpromazine (CP), a clathrin-mediated endocytosis inhibitor, or 1 mM methyl-b-cyclodextrin (MB), a caveolin-mediated endocytosis inhibitor (Thompson et al 2006, Kelley et al 2009, Masaike et al 2010. Western blot analysis Cells (10 5 ) were plated in sixwell plates and cultured in F-12 medium containing 5% FCS.…”
Section: Procedures Of Immunohistochemistry Formentioning
confidence: 99%